1996
DOI: 10.1093/bja/77.6.758
|View full text |Cite
|
Sign up to set email alerts
|

Antinociception by intrathecal midazolam involves endogenous neurotransmitters acting at spinal cord delta opioid receptors

Abstract: Intrathecal midazolam causes antinociception by combining with spinal cord benzodiazepine receptors. This effect is reversible with doses of naloxone, suggesting involvement of spinal kappa or delta but not mu opioid receptors. The antinociceptive effects of intrathecally administered drugs in the spinal cord were demonstrated by measurements of the electrical current threshold for avoidance behaviour in rats with chronically implanted lumbar intrathecal catheters. A comparison was made of suppression by two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 12 publications
1
40
0
2
Order By: Relevance
“…20 It has also been suggested that intrathecal midazolam is involved in the release of an endogenous opioid acting at spinal delta receptors. 21 Yegin et al 1 reported that addition of 25 μg fentanyl to 18 mg hyperbaric ropivacaine for spinal anesthesia in patients undergoing transurethral resection of the prostate provided postoperative analgesia of approximately 3.5 h; 4 out of 15 patients in fentanyl group had pruritus. Though, the analgesic efficacy of intrathecal fentanyl has not been compared with intrathecal midazolam in normal patients, a recent study demonstrated that addition of 1 mg intrathecal midazolam to bupivacaine produces much longer duration of anesthesia (140 min) as compared with 25 μg intrathecal fentanyl (107 min) in opium abusers undergoing lower limb orthopedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…20 It has also been suggested that intrathecal midazolam is involved in the release of an endogenous opioid acting at spinal delta receptors. 21 Yegin et al 1 reported that addition of 25 μg fentanyl to 18 mg hyperbaric ropivacaine for spinal anesthesia in patients undergoing transurethral resection of the prostate provided postoperative analgesia of approximately 3.5 h; 4 out of 15 patients in fentanyl group had pruritus. Though, the analgesic efficacy of intrathecal fentanyl has not been compared with intrathecal midazolam in normal patients, a recent study demonstrated that addition of 1 mg intrathecal midazolam to bupivacaine produces much longer duration of anesthesia (140 min) as compared with 25 μg intrathecal fentanyl (107 min) in opium abusers undergoing lower limb orthopedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 It also causes release of endogenous opioid acting at spinal delta receptors as naltrinadole, a delta receptor opioid antagonist suppresses its analgesic effect. 28 Thirdly it inhibits adenosine uptake or enhance adenosine release. 25 The use of IT midazolam in humans is reported in at least 18 peer reviewed reports in about 797 patients since 1986.…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam administered via intrathecal or epidural routes can produce analgesia, probably due to its GABA mediated action [4]. Other mechanisms of action including its interaction with opiate receptors have also been proposed [10].…”
Section: Midazolammentioning
confidence: 99%
“…In 1990s, analgesic efficacy of intrathecal midazolam in humans has been demonstrated [7][8][9]. Naltrindole, a δ-selective opioid antagonistic agent, suppresses the antinociceptive effect of intrathecal midazolam, suggesting that intrathecal midazolam is involved in the release of an endogenous opioid acting at spinal δ receptors [10].…”
Section: Introductionmentioning
confidence: 99%